Development of graphene based transparent electrode - Goh, Wei Liang. (2013)
Graphene based transparent electrode was developed with the technique of spin coating of Ag nanowire (NW) and graphene oxide (GO). The best properties obtain with this method is was optical transmittance of 82.2% at 700 nm light and 80.1% at 550 nm light with 1mm thick PC substrate included and sheet resistance of 205.6 Ω/sq . The exponential relationship between GO and sheet resistance was discussed and the plateau region was found to be at 300μL for